Unravelling the complex nature of the Upper Weichselian till section at Gdynia Babie Doły, northern Poland - Woźniak, Piotr Paweł; Czubla, Piotr (Adam Mickiewicz University Poznan, 2016)
The complexity of glacial sequences may increase when these formed underneath ice sheets despite subsequent changes in their extent that are accompanied by alterations in the direction of the ice flow. Our aim was to determine whether or not changes in ice sheet dynamics during the Late Weichselian are also recorded in sediments formed north of the area of its fluctuating margin (i.e., where the ice sheet prevailed independent of such fluctuations). It is shown that in these areas such a record could have occurred, as documented by results of till studies at Babie Doły. The examination was carried out using several analyses: lithofacies properties of sediments, petrographic till composition (fine gravel fraction, indicator erratics), till matrix CaCO3 content, till fabric, as well as orientation of striae on the top surfaces of large clasts. In parallel, datings of sub- and supra-till sediments using the TL method were carried out. The basal till at Babie Doły represents almost the entire Upper Weichselian, but it can be divided into subunits whose features indicate different ice flow directions and debris supply. The lower subunit developed as a result of the palaeo-ice stream along the main axis of the Baltic Sea (from the north), expanding to areas adjacent to the depression of the Gulf of Gdańsk. The upper subunit developed when the influence of the palaeo-ice stream in the study area decreased, the main role having been taken over by the ice flowing from the northwest. The till analysed also shows considerable lateral variation, indicative of the mosaic nature of subglacial sedimentation. We consider the diversity of permeability of deposits over which the ice sheet extended to be the prime factor that determined such a situation.